Ultrasound-guided transversus abdominis plane block: An evaluation of its efficacy in reducing post-operative opioid requirements in caesarean section - Shahid Adeel; Priti Narayan; Mahesh M Chandrashekaraiah; Khadija A Abuhassan; Rahma M Elsemeen; Sharon Skowronski (Wolters Kluwer Medknow Publications, 2017)
Background: Different volumes of local anaesthetic are employed in transversus abdominis plane (TAP) block to provide analgesia for lower abdominal surgeries. Our aim was to compare the efficacy of high versus low volume of bupivacaine TAP block in providing postoperative analgesia for caesarean sections. Settings and Design: Prospective, single-blind, randomized comparative study was performed during post-operative period. Materials and Methods: Sixty patients who had received spinal anaesthesia for caesarean section were randomly allocated to one of three groups: Group A received 20 ml of 0.25% bupivacaine, Group B received 30 ml of 0.166% bupivacaine on each side TAP block under ultrasound guidance, respectively, and Group C did not receive TAP block. Multi-modal analgesia comprising paracetamol, diclofenac and patient-controlled analgesia (PCA) morphine was administered to all patients. The primary outcome measure in our study was 24-h post-operative morphine consumption through intravenous (IV) PCA. Other secondary outcome measures were pain scores, nausea, sedation and patient satisfaction scores. Statistical Analysis: Statistical analysis done using analysis of variance, Fisher's Exact test and Kruskal-Wallis test. Results: Our primary outcome measure of 24-h cumulative PCA morphine consumption was 18.2 ± 6.5, 17.9 ± 8.6 and 19.4 ± 8.4 mg in groups A, B and C, respectively (P = 0.819). In the secondary outcome measures, 100% of study population in group A & B and 95% of group C had pain score of 0-3 on Numerical Rating Scale (P = 1.000) at 24 hr. 19, 15 and17 patients in group A, B and C, respectively, agreed and 1, 5 and 3 patients in group A, B and C, respectively, very strongly agreed with patient satisfaction survey for pain management (P = 0.265). Conclusion: TAP block as a part of multi-modal analgesia is debatable in the context of reducing the need of post-operative opioids. The present study was unequivocal in that two different volumes of same dose of local anaesthetic failed to demonstrate any clinical or statistical significance in decreasing post-operative opioid consumption following caesarean section.